Cobalt-coated nickel-containing hydroxide particles
Cobalt-coated nickel-containing hydroxide particles with a specific composition and coating layer design address the issue of electrical conductivity loss in nickel-hydrogen secondary batteries under high stress conditions, achieving enhanced battery performance.
Patent Information
- Application Number
- JP2020215563
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-18
- Filing Date
- 2020-12-24
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-12-24
AI Technical Summary
Existing nickel-hydrogen secondary battery positive electrode active materials face challenges in maintaining electrical conductivity, especially under high temperatures and high loads, due to aggregation of nickel-containing hydroxide particles when the cobalt coating is oxidized.
Cobalt-coated nickel-containing hydroxide particles with a specific mole % ratio of nickel:zinc:added metal elements and a coating layer containing cobalt oxyhydroxide are developed. These particles are designed to prevent aggregation during cobalt oxidation, maintaining reduced volume resistivity.
The solution effectively prevents the decrease in electrical conductivity of the positive electrode active material, even under harsh conditions like high temperatures and high loads, resulting in improved battery characteristics.
Smart Images

Figure 0007659986000003 
Figure 0007659986000004 
Figure 0007659986000001
Abstract
Description
[Technical field]
[0001] The present invention relates to cobalt-coated nickel-containing hydroxide particles, which can reduce volume resistivity by preventing aggregation of the nickel-containing hydroxide particles when the cobalt coating of the nickel-containing hydroxide particles is oxidized, and which can improve battery characteristics when used as a positive electrode active material for a secondary battery. [Background technology]
[0002] In recent years, with the increasing sophistication of devices, there is an increasing demand for improved battery characteristics of secondary batteries such as nickel-metal hydride batteries. In response to this, nickel-containing composite hydroxide particles with an increased cobalt content have been developed to improve the battery characteristics of cobalt compound-coated nickel hydroxide particles for use as positive electrode active materials in secondary batteries.
[0003] In addition, in order to increase the cobalt content, a coating layer containing a high content of cobalt compound is formed on nickel hydroxide particles. For example, nickel hydroxide particles having a coating layer of a cobalt compound are coated with nickel hydroxide powder particles having a surface coated with a cobalt compound mainly composed of cobalt oxyhydroxide or a mixture of cobalt oxyhydroxide and cobalt hydroxide to ensure the uniformity and adhesion of the coating layer. A coated nickel hydroxide powder for use as a positive electrode active material in an alkaline secondary battery has been proposed (Patent Document 1), which is characterized in that the valence of cobalt in the coating is 2.5 or more, and the amount of coating that peels off when 20 g of the coated nickel hydroxide powder is shaken in a sealed container for 1 hour is 20 mass % or less of the total coating amount.
[0004] On the other hand, due to the further enhancement of the functionality of devices equipped with secondary batteries such as nickel-hydrogen secondary batteries, it is necessary for the secondary batteries to exhibit excellent characteristics even under harsh environments such as high temperatures or when a high load is applied. When evaluating the charge / discharge capacity of secondary batteries such as nickel-hydrogen secondary batteries at high temperatures, there have been cases where the electrical conductivity of the positive electrode active material is reduced, and as a result, excellent charge / discharge capacity cannot be obtained. Therefore, it is necessary to prevent the electrical conductivity of the positive electrode active material from decreasing even when secondary batteries such as nickel-hydrogen secondary batteries are in harsh environments such as high temperatures or when a high load is applied.
[0005] However, in the coated nickel hydroxide powder for use as a positive electrode active material in an alkaline secondary battery described in Patent Document 1, the electrical conductivity of the positive electrode active material may decrease when the battery is charged and discharged under high load, leaving room for improvement in terms of improving the electrical conductivity of the positive electrode active material. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2014-103127 A Summary of the Invention [Problem to be solved by the invention]
[0007] In view of the above circumstances, the present invention aims to provide cobalt-coated nickel-containing hydroxide particles that can reduce volume resistivity by preventing aggregation of the nickel-containing hydroxide particles when the cobalt coating of the nickel-containing hydroxide particles is oxidized. [Means for solving the problem]
[0008] The gist of the configuration of the present invention is as follows. [1] Cobalt-coated nickel-containing hydroxide particles in which a coating layer containing cobalt oxyhydroxide as a main component is formed on nickel-containing hydroxide particles, The nickel-containing hydroxide particles contain nickel (Ni), zinc (Zn), and one or more added metal elements M selected from the group consisting of cobalt (Co) and magnesium (Mg), and the molar ratio of nickel:zinc:added metal element M is 100-xy:x:y (meaning 1.50≦x≦9.00, 0.00≦y≦3.00); In a volume-based particle size distribution measured by a laser diffraction scattering method, the maximum peak has a height a, there is one peak at a height of (1 / 2)a or more, and the value A of the following formula (1) is calculated from the width b of the maximum peak at a height of (1 / 2)a, Cobalt-coated nickel-containing hydroxide particles, in which a volume-based particle size distribution measured by a laser diffraction scattering method after compression treatment at a press pressure of 64 MPa has a maximum peak with a height c, and has a value B of the following formula (2) calculated from a width d of the maximum peak at a height of (1 / 2)c, and the value B and the value A have a relationship represented by the following formula (3). A = [(b × (1 / 2)a] / 2 (1) B = [(d × (1 / 2)c] / 2 (2) -1.50≦[(BA) / A]×100≦5.00 ···(3) [2] The cobalt-coated nickel-containing hydroxide particles according to [1], wherein the volume-based particle size distribution before the compression treatment has one peak. [3] The cobalt-coated nickel-containing hydroxide particles according to [1] or [2], having a volume resistivity of 0.40 Ω·cm or more and 1.20 Ω·cm or less. [4] The cobalt-coated nickel-containing hydroxide particles according to any one of [1] to [3], wherein the coating layer containing cobalt oxyhydroxide further contains cobalt oxide. [5] The cobalt-coated nickel-containing hydroxide particles according to any one of [1] to [4], wherein the nickel-containing hydroxide particles contain zinc. [6] The cobalt-coated nickel-containing hydroxide particles according to any one of [1] to [5], which are used as a positive electrode active material for a nickel-hydrogen secondary battery. [7] A positive electrode comprising the cobalt-coated nickel-containing hydroxide particles according to any one of [1] to [6] and a metal foil current collector. [8] A nickel-metal hydride secondary battery comprising the positive electrode according to [7].
[0009] The cobalt-coated nickel-containing hydroxide particles of the present invention are nickel-containing hydroxide particles having a coating layer, and the coating layer contains a cobalt compound.
[0010] In the above aspect [1], "volume-based particle size distribution by laser diffraction scattering method" means a volume-based particle size distribution measured by laser diffraction scattering method under the following conditions: solvent: water, solvent refractive index: 1.33, particle refractive index: 2.13, transmittance: 80±5%, dispersion medium: 10.0 wt% sodium hexametaphosphate aqueous solution. Also, "compression treatment at a press pressure of 64 MPa" means that 3.00 g of the sample was placed in a sample-injection cell with a radius of 10 mm, and compressed therein with a load of 20 kN.
[0011] In the above embodiment [1], the maximum peak of the cobalt-coated nickel-containing hydroxide particles before compression treatment has a single peak in a region having a height equal to or greater than half the height a of the maximum peak, and the peak is not split. Effect of the Invention
[0012] According to the cobalt-coated nickel-containing hydroxide particles of the present invention, the nickel-containing hydroxide particles contain nickel, zinc, and one or more added metal elements M selected from the group consisting of cobalt and magnesium, the molar ratio of nickel:zinc:added metal element M is 100-xy:x:y (meaning 1.50≦x≦9.00, 0.00≦y≦3.00), and in a volume-based particle size distribution by a laser diffraction scattering method, the maximum peak has a height a, there is one peak at a height of (1 / 2)a or more, and the following formula (1) calculated from the width b of the maximum peak at a height of (1 / 2)a is satisfied: ) value A, and in a volume-based particle size distribution measured by a laser diffraction scattering method after compression treatment at a press pressure of 64 MPa, the maximum peak has a height c and has a value B of the following formula (2) calculated from the width d of the maximum peak at a height of (1 / 2)c. The relationship between the value B and the value A is expressed by the following formula (3), so that when the cobalt coating of the nickel-containing hydroxide particles is oxidized, aggregation of the nickel-containing hydroxide particles is prevented while the cobalt coating is sufficiently oxidized, and thus it is possible to obtain cobalt-coated nickel-containing hydroxide particles with reduced volume resistivity. A = [(b × (1 / 2)a] / 2 (1) B = [(d × (1 / 2)c] / 2 (2) -1.50≦[(BA) / A]×100≦5.00 ···(3)
[0013] Therefore, when a positive electrode active material using the cobalt-coated nickel-containing hydroxide particles of the present invention is installed in a secondary battery, the secondary battery can be operated in harsh environments such as high temperatures and under high loads, and the electrical conductivity of the positive electrode active material can be prevented from decreasing, thereby enabling the battery to exhibit excellent battery characteristics.
[0014] The cobalt-coated nickel-containing hydroxide particles of the present invention have a volume resistivity of 1.20 Ω cm or less. Therefore, even when the secondary battery is operated in a severe environment such as at high temperature and under a high load, the positive electrode active material can more reliably exhibit excellent electrical conductivity, and therefore excellent battery characteristics can be more reliably exhibited. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is an explanatory diagram of the region indicated by value A in formula (1) in the volume-based particle size distribution diagram of the cobalt-coated nickel-containing hydroxide particles of the present invention. [Diagram 2] FIG. 2 is a volume-based particle size distribution diagram obtained by a laser diffraction scattering method for the cobalt-coated nickel-containing hydroxide particles of the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The cobalt-coated nickel-containing hydroxide particles of the present invention will be described in detail below. The cobalt-coated nickel-containing hydroxide particles of the present invention have a coating layer of a cobalt compound formed on the surface of the nickel-containing hydroxide particles. That is, the nickel-containing hydroxide particles are core particles, and the core particles are coated with a layer of a cobalt compound (shell structure), for example, a layer of a cobalt compound whose valence of cobalt is mainly trivalent. An example of the cobalt compound whose valence of cobalt is trivalent is cobalt oxyhydroxide. From the above, the cobalt-coated nickel-containing hydroxide particles of the present invention are particles in which a coating layer containing cobalt oxyhydroxide is formed on the nickel-containing hydroxide particles.
[0017] The shape of the cobalt-coated nickel-containing hydroxide particles is not particularly limited, but may be, for example, substantially spherical. The nickel-containing hydroxide particles are, for example, in the form of secondary particles formed from a plurality of primary particles. The coating layer containing cobalt oxyhydroxide of the cobalt-coated nickel-containing hydroxide particles may cover the entire surface of the nickel-containing hydroxide particles, or may cover a partial area of the surface of the nickel-containing hydroxide particles.
[0018] The cobalt-coated nickel-containing hydroxide particles of the present invention have a maximum peak with a height a in a volume-based particle size distribution measured by a laser diffraction scattering method, one peak at a height of (1 / 2)a or more, and a value A of the following formula (1) calculated from the width b of the maximum peak at a height of (1 / 2)a. A = [(b × (1 / 2)a] / 2 (1)
[0019] The cobalt-coated nickel-containing hydroxide particles of the present invention are used, for example, as a positive electrode active material for nickel-hydrogen secondary batteries. Therefore, the cobalt-coated nickel-containing hydroxide particles of the present invention, which are products used as positive electrode active materials, have a maximum peak height (i.e., maximum frequency) of a in a volumetric particle size distribution diagram obtained by a laser diffraction scattering method, and the maximum peak has only one peak in a region of height (frequency) of (1 / 2)a or more. In addition, in the volumetric particle size distribution diagram, the width of the maximum peak at a height of (1 / 2)a is b, and the value of formula (1) calculated from the maximum peak height a and the maximum peak width b is A. The value A of the above formula (1) indicates the extent of the area size of the region where the maximum peak height is 1 / 2 or more for the maximum peak in the volumetric particle size distribution diagram of the cobalt-coated nickel-containing hydroxide particles of the present invention, which are products.
[0020] Furthermore, the cobalt-coated nickel-containing hydroxide particles of the present invention have a maximum peak with height (i.e., maximum frequency) c in a volumetric particle size distribution measured by a laser diffraction scattering method after compression treatment at a press pressure of 64 MPa, and have a value B of the following formula (2) calculated from the width d of the maximum peak at a height (frequency) of (1 / 2)c. The value B of the following formula (2) indicates the extent of the area size of a region in which the height of the maximum peak is 1 / 2 or more of the maximum peak in the volumetric particle size distribution diagram after compression treatment of the cobalt-coated nickel-containing hydroxide particles of the present invention. B = [(d × (1 / 2)c] / 2 (2)
[0021] The cobalt-coated nickel-containing hydroxide particles of the present invention have different shapes of the maximum peaks in a volume-based particle size distribution diagram obtained by a laser diffraction scattering method before and after compression treatment at a press pressure of 64 MPa.
[0022] As described later, the cobalt-coated nickel-containing hydroxide particles of the present invention can be obtained by forming a coating layer containing cobalt on the surface of a nickel-containing hydroxide particle, which is a core particle, to obtain nickel-containing hydroxide particles having a coating layer formed thereon, and then adding an alkaline solution to the nickel-containing hydroxide particles having a coating layer formed thereon to oxidize the cobalt contained in the coating layer to form cobalt oxyhydroxide.
[0023] When an alkaline solution is added to nickel-containing hydroxide particles having a coating layer to oxidize the cobalt contained in the coating layer, if the oxidation of the cobalt contained in the coating layer is insufficient due to an insufficient amount of the alkaline solution, the nickel-containing hydroxide particles having a coating layer are unlikely to aggregate, but the oxidation to cobalt oxyhydroxide is insufficient. Therefore, the electrical conductivity of the positive electrode active material is reduced. On the other hand, when an alkaline solution is added to nickel-containing hydroxide particles having a coating layer to oxidize the cobalt contained in the coating layer, if the amount of the alkaline solution added is excessive, the oxidation of the cobalt contained in the coating layer is promoted, but the nickel-containing hydroxide particles having a coating layer are likely to aggregate due to the action of the alkaline solution. When the nickel-containing hydroxide particles having a coating layer aggregate, an aggregation site is formed where the nickel-containing hydroxide particles having a coating layer are in contact with each other. Since the coating layer is not exposed at the aggregation site, the oxidation of the cobalt contained in the coating layer is inhibited. For example, when the aggregated cobalt-coated nickel-containing hydroxide particles are cracked before or after being mounted on a positive electrode, exposing the aggregated portion, the electrical conductivity of the positive electrode active material is reduced. In addition, when the nickel-containing hydroxide particles on which the coating layer is formed are aggregated, the handling properties are reduced when the cobalt-coated nickel-containing hydroxide particles are filled into a positive electrode current collector as a positive electrode active material, which may affect the characteristics of the positive electrode and, ultimately, the battery characteristics.
[0024] The inventors have found that the degree of agglomeration and the degree of oxidation during the oxidation treatment of nickel-containing hydroxide particles having a coating layer formed thereon can be measured by compressing the cobalt-coated nickel-containing hydroxide particles obtained as a product at a press pressure of 64 MPa and analyzing the difference in the maximum peak of the volume-based particle size distribution measured by a laser diffraction scattering method before and after the compression treatment.
[0025] Specifically, the present inventors have found that, in analyzing the difference in the maximum peak of the volumetric particle size distribution described above, the degree of occurrence of aggregation and the degree of oxidation in the oxidation treatment of nickel-containing hydroxide particles having a coating layer formed thereon can be measured by analyzing the difference in the area of the region where the height of the maximum peak is 1 / 2 or more for the maximum peak of the volumetric particle size distribution diagram. The reason why the degree of occurrence of aggregation and the degree of oxidation in the oxidation treatment of nickel-containing hydroxide particles having a coating layer formed thereon can be measured by analyzing the difference in the area of the region where the height of the maximum peak is 1 / 2 or more for cobalt-coated nickel-containing hydroxide particles is believed to be because the area of the region where the height of the maximum peak is 1 / 2 or more indicates the reaction efficiency between the cobalt-coated nickel-containing hydroxide particles and the alkaline solution.
[0026] FIG. 1 illustrates the maximum peak of the volumetric particle size distribution in terms of the area of the region where the height (frequency) of the maximum peak is 1 / 2 or more as described above. FIG. 1 is an explanatory diagram showing an overview of the value A of formula (1) in the volumetric particle size distribution diagram of the cobalt-coated nickel-containing hydroxide particles of the present invention. In FIG. 1, the cobalt-coated nickel-containing hydroxide particles of the present invention have one peak in the volumetric particle size distribution. Note that the value B of formula (2) can also be illustrated in terms of the area of the region where the height of the maximum peak is 1 / 2 or more in the same manner as in FIG. 1.
[0027] The present inventors also found that if an excessive amount of alkaline solution is added, the nickel-containing hydroxide particles on which a coating layer is formed may undergo aggregation during oxidation treatment, resulting in the maximum peak having multiple peaks in a region where the maximum peak height is 1 / 2 or more. In other words, the inventors found that by preventing the addition of an excessive amount of alkaline solution, the maximum peak has only one peak in a region where the maximum peak height is 1 / 2 or more.
[0028] If the oxidation of the cobalt contained in the coating layer is insufficient due to an insufficient amount of alkaline solution added, the nickel-containing hydroxide particles on which the coating layer is formed will not aggregate much, but the compression treatment will cause the nickel-containing hydroxide particles with the coating layer insufficiently oxidized cobalt to adhere to each other and become difficult to disperse, and it is believed that the area of the region where the maximum peak height is 1 / 2 or more will be greatly decreased or increased by the compression treatment. On the other hand, if the amount of alkaline solution added is excessive when the alkaline solution is added to oxidize the cobalt contained in the coating layer, the nickel-containing hydroxide particles on which the coating layer is formed will tend to aggregate, and the particles that were aggregated by the compression treatment will break into multiple pieces mainly at the aggregation sites, and it is believed that the area of the region where the maximum peak height is 1 / 2 or more will be greatly decreased or increased by the compression treatment.
[0029] From the above, the cobalt-coated nickel-containing hydroxide particles of the present invention have a relationship of the following formula (3) between the value A before compression treatment at a pressing pressure of 64 MPa calculated by formula (1) and the value B after compression treatment at a pressing pressure of 64 MPa calculated by formula (2). That is, the change in the area of the maximum peak in the volumetric particle size distribution diagram by the laser diffraction scattering method before and after compression treatment at a pressing pressure of 64 MPa is controlled to be within the range of the following formula (3). The following formula (3) means the relative error between the value A before compression treatment at a pressing pressure of 64 MPa and the value B after compression treatment at a pressing pressure of 64 MPa. -1.50≦[(BA) / A]×100≦5.00 ···(3)
[0030] The value A before compression treatment at a pressure of 64 MPa calculated by formula (1) and the value B after compression treatment at a pressure of 64 MPa calculated by formula (2) have the relationship of the above formula (3), that is, the value of [(BA) / A]×100 is within the range of −1.50 to 5.00, which indicates that when the cobalt coating of the nickel-containing hydroxide particles is oxidized, the cobalt coating is sufficiently oxidized to generate cobalt oxyhydroxide while preventing the nickel-containing hydroxide particles from agglomerating, and therefore it is possible to obtain cobalt-coated nickel-containing hydroxide particles with reduced volume resistivity. Therefore, when the positive electrode active material using the cobalt-coated nickel-containing hydroxide particles of the present invention is mounted on a secondary battery, and the secondary battery is operated under a severe environment such as high temperature and is also under a high load, the electrical conductivity of the positive electrode active material can be prevented from decreasing, and excellent battery characteristics can be exhibited.
[0031] The value of [(BA) / A]×100 calculated by formula (3) is not particularly limited as long as it is in the range of -1.50 to 5.00, but the lower limit is preferably -1.40, and particularly preferably -1.30, in that the aggregation of the nickel-containing hydroxide particles is more reliably prevented while the cobalt coating is more reliably oxidized to generate cobalt oxyhydroxide. On the other hand, the upper limit of [(BA) / A]×100 calculated by formula (3) is preferably 4.50, more preferably 3.00, and particularly preferably 1.50. The above upper limit and lower limit can be combined in any way.
[0032] The shape of the volumetric particle size distribution diagram obtained by the laser diffraction scattering method is not particularly limited, but a shape having one peak in the volumetric particle size distribution is preferable in terms of improving the loading density of the positive electrode active material in the positive electrode.
[0033] The volume resistivity of the cobalt-coated nickel-containing hydroxide particles of the present invention is not particularly limited, but is preferably 1.20 Ω·cm or less, more preferably 1.10 Ω·cm or less, and particularly preferably 1.00 Ω·cm or less, from the viewpoint of more reliably improving the electrical conductivity of the cobalt-coated nickel-containing hydroxide particles. On the other hand, the lower the lower limit of the volume resistivity of the cobalt-coated nickel-containing hydroxide particles, the more preferable. The lower limit of the volume resistivity of the cobalt-coated nickel-containing hydroxide particles is, for example, 0.40 Ω·cm. By more reliably improving the electrical conductivity of the cobalt-coated nickel-containing hydroxide particles of the present invention, a secondary battery equipped with the cobalt-coated nickel-containing hydroxide particles of the present invention as a positive electrode active material can operate under severe conditions such as high temperatures and even under high load conditions, and therefore the positive electrode active material can more reliably exhibit excellent electrical conductivity, thereby more reliably exhibiting excellent battery characteristics.
[0034] In addition, the coating layer containing cobalt oxyhydroxide of the cobalt-coated nickel-containing hydroxide particles of the present invention may further contain cobalt oxide. The fact that the coating layer containing cobalt oxyhydroxide further contains cobalt oxide indicates that when an alkaline solution is added to the nickel-containing hydroxide particles on which a coating layer is formed to oxidize the cobalt contained in the coating layer, the nickel-containing hydroxide particles on which a coating layer is formed are prevented from easily agglomerating due to the addition of an excessive amount of alkaline solution.
[0035] The nickel-containing hydroxide particles, which are core particles, are particles of hydroxide containing nickel, and further contain zinc (Zn) in order to obtain a high utilization rate and excellent charge / discharge characteristics. Furthermore, the zinc contained in the nickel-containing hydroxide particles is preferably in the form of solid solution zinc. From the above, the nickel-containing hydroxide particles, which are core particles, are particles of nickel hydroxide in which zinc is solid-solved, i.e., nickel-containing composite hydroxide particles.
[0036] The nickel-containing hydroxide particles, which are the core particles, may contain not only zinc (Zn) but also cobalt (Co) and magnesium (Mg) as a solid solution, if necessary, in order to extend the life of the nickel-containing hydroxide particles.
[0037] When the nickel-containing hydroxide particles contain dissolved cobalt, it is preferable that at least a part of the dissolved cobalt is trivalent cobalt in order to further improve the electrical conductivity of the nickel-containing hydroxide particles. An example of the trivalent cobalt dissolved in the nickel-containing hydroxide particles is cobalt oxyhydroxide.
[0038] The nickel-containing hydroxide particles that are core particles include nickel (Ni), zinc (Zn), and one or more additive metal elements M selected from the group consisting of cobalt (Co) and magnesium (Mg), and the molar ratio of nickel:zinc:additive metal element M is 100-xy:x:y (meaning 1.50≦x≦9.00, 0.00≦y≦3.00). The additive metal element M is preferably in solid solution in the nickel-containing hydroxide particles. The value of x is not particularly limited as long as it is 1.50 or more and 9.00 or less, but is preferably 1.60 or more and 5.00 or less, more preferably 1.70 or more and 4.00 or less, and particularly preferably 1.80 or more and 3.00 or less. The value of y is not particularly limited as long as it is 0.00 to 3.00, but is more preferably 0.00 to 2.50, even more preferably 0.00 to 2.25, and particularly preferably 0.00 to 2.00, from the viewpoint that the added metal element M in the core particle does not inhibit the oxidation of the coating layer in the oxidation step and the oxidation treatment can be performed at a high temperature. The value of 100-xy, which is the mole percent ratio of nickel related to the battery capacity, is not particularly limited as long as it is 88.00 to 98.5, but is more preferably 92.00 to 98.40, even more preferably 93.00 to 98.30, and particularly preferably 94.00 to 98.20.
[0039] An example of a method for analyzing metal elements in nickel-containing hydroxide particles is analysis by ICP (inductively coupled plasma) optical emission spectrometry, etc. Also, an example of a method for analyzing metal elements contained in core particles after cobalt coating is analysis by EDX (energy dispersive X-ray) of the core particle part of the particle cross section, which is cut into cobalt-coated nickel-containing hydroxide particles.
[0040] The cobalt oxyhydroxide contained in the coating layer has a diffraction peak at a diffraction angle represented by 2θ of 65° to 66° in the diffraction pattern obtained by X-ray diffraction measurement.
[0041] The nickel content in the nickel-containing hydroxide particles in the cobalt-coated nickel-containing hydroxide particles is not particularly limited, but the lower limit is preferably 40 mass%, more preferably 45 mass%, and particularly preferably 50 mass%. On the other hand, the upper limit of the nickel content in the nickel-containing hydroxide particles in the cobalt-coated nickel-containing hydroxide particles is preferably 65 mass%, and particularly preferably 60 mass%. The above-mentioned lower limit and upper limit can be combined arbitrarily.
[0042] The average particle size of the cobalt-coated nickel-containing hydroxide particles is not particularly limited, but for example, the lower limit of the particle size (D50) at a cumulative volume percentage of 50% by volume (hereinafter, simply referred to as "D50") is preferably 4.0 μm, more preferably 6.0 μm, and particularly preferably 9.0 μm, from the viewpoint of reliably preventing the aggregation of the nickel-containing hydroxide particles when the cobalt coating of the nickel-containing hydroxide particles is oxidized. On the other hand, the upper limit of the D50 of the cobalt-coated nickel-containing hydroxide particles is preferably 15.0 μm, and particularly preferably 12.5 μm, from the viewpoint of a balance between improving the packing density and ensuring the contact surface with the electrolyte. The above-mentioned lower limit and upper limit can be combined arbitrarily. The D50 of the cobalt-coated nickel-containing hydroxide particles can be measured, for example, when measuring the volume-based particle size distribution by a laser diffraction scattering method.
[0043] The BET specific surface area of the cobalt-coated nickel-containing hydroxide particles is not particularly limited, but the lower limit is 5.0 m from the viewpoint of a balance between improving density and ensuring a contact surface with the electrolyte. 2 / g is preferred, and 10.0m 2 On the other hand, the upper limit of the BET specific surface area of the cobalt-coated nickel-containing hydroxide particles is 20.0 m / g in terms of obtaining excellent particle strength. 2 / g is preferred, and 15.0m 2 The above lower limit and upper limit can be combined in any desired manner.
[0044] The tap density of the cobalt-coated nickel-containing hydroxide particles is not particularly limited, but is preferably 1.5 g / cm3 from the viewpoint of improving the packing density when used in a positive electrode as a positive electrode active material. 3 More than 1.7 g / cm is preferable. 3 The above is particularly preferred.
[0045] The bulk density of the cobalt-coated nickel-containing hydroxide particles is not particularly limited, but is preferably 0.8 g / cm3 from the viewpoint of improving the packing density when used in a positive electrode as a positive electrode active material. 3 More than 1.0 g / cm is preferable. 3 The above is particularly preferred.
[0046] Next, an example of a method for producing the cobalt-coated nickel-containing hydroxide particles of the present invention will be described.
[0047] The method for producing the cobalt-coated nickel-containing hydroxide particles of the present invention includes, for example, a step of preparing a suspension (e.g., an aqueous suspension) containing nickel-containing hydroxide particles, which are core particles; a coating step of supplying a cobalt salt solution and an alkaline solution to the suspension containing the nickel-containing hydroxide particles to form a coating layer containing cobalt on the surface of the nickel-containing hydroxide particles, thereby obtaining nickel-containing hydroxide particles having a coating layer formed thereon; and an oxidation step of adding an alkaline solution to the nickel-containing hydroxide particles having a coating layer formed thereon, mixing, and heating to oxidize the cobalt contained in the coating layer.
[0048] <Preparation step of suspension containing nickel-containing hydroxide particles> A method for preparing a suspension containing nickel-containing hydroxide particles, which are core particles, will be described below. Here, a method for preparing a suspension containing nickel-containing hydroxide particles in which zinc and an added metal element M are dissolved will be described as an example. First, a salt solution of nickel, zinc, and the added metal element M, to which nickel, zinc, and the added metal element M are added at a predetermined mixing ratio, is reacted with a complexing agent by a coprecipitation method to produce nickel-containing hydroxide particles, thereby obtaining a slurry-like suspension containing nickel-containing hydroxide particles. For example, water is used as the solvent for the suspension.
[0049] The complexing agent is not particularly limited as long as it can form a complex with ions of nickel, zinc, and the added metal element M in an aqueous solution, and examples thereof include ammonium ion donors (ammonium sulfate, ammonium chloride, ammonium carbonate, ammonium fluoride, etc.), hydrazine, ethylenediaminetetraacetic acid, nitrilotriacetic acid, uracildiacetic acid, and glycine. In the coprecipitation, an alkali metal hydroxide (e.g., sodium hydroxide, potassium hydroxide) is added as necessary to adjust the pH value of the aqueous solution.
[0050] When the salt solution and the complexing agent are continuously supplied to the reaction vessel, nickel, zinc and the added metal element M undergo a crystallization reaction, producing nickel-containing hydroxide particles. During the crystallization reaction, the temperature of the mother liquor in the reaction vessel is controlled within a range of, for example, 10°C to 80°C, preferably 20 to 70°C, and the material in the reaction vessel is appropriately stirred while controlling the pH value of the mother liquor in the reaction vessel within a range of, for example, pH 9 to pH 13, preferably pH 11 to 13, based on a liquid temperature of 25°C. The reaction vessel may be, for example, a continuous type in which the formed nickel-containing hydroxide particles are overflowed to separate them.
[0051] <Solid-liquid separation process> Next, the suspension containing the nickel-containing hydroxide particles is separated into a solid phase and a liquid phase, and the solid phase separated from the liquid phase is dried to obtain a dry powder of the nickel-containing hydroxide particles formed from the slurry suspension. Furthermore, before drying the solid phase, the solid phase may be washed with weak alkaline water as necessary.
[0052] <Coating process> Next, the dry powder of nickel-containing hydroxide particles is mixed with 45°C hot water at a predetermined weight ratio and fed to a reaction tank, and then the hot water is added to obtain a predetermined suspension concentration. By mixing the dry powder with hot water in advance before the start of the reaction, the dry powder is sufficiently soaked in hot water, and it becomes easy to react with the cobalt salt solution. The weight ratio of the dry powder to the hot water is not particularly limited, but is preferably 1.0:2.0, more preferably 1.0:2.5, and particularly preferably 1.0:3.0. Then, a cobalt salt solution (e.g., an aqueous solution of cobalt sulfate, etc.) and an alkaline solution (e.g., an aqueous solution of sodium hydroxide, etc.) are added while stirring with a stirrer, and a coating layer mainly composed of a cobalt compound with a valence of cobalt of divalent, such as cobalt hydroxide, is formed on the surface of the nickel-containing hydroxide particles by neutralization crystallization. At this time, an ammonium ion donor (e.g., an ammonium sulfate solution, etc.) may be added as a complexing agent. The pH of the step of forming the coating layer is preferably maintained in the range of 9 to 13 based on a liquid temperature of 25° C. The coating step can provide nickel-containing hydroxide particles having a coating layer containing cobalt formed thereon. The nickel-containing hydroxide particles having a coating layer containing cobalt formed thereon can be obtained as a slurry-like suspension.
[0053] <Solid-liquid separation process> A suspension containing nickel-containing hydroxide particles having a coating layer containing cobalt formed thereon is separated into a solid phase and a liquid phase, and the solid phase separated from the liquid phase is dried, whereby a dry powder of nickel-containing hydroxide particles having a coating layer containing cobalt formed thereon can be obtained from the slurry suspension. Furthermore, before drying the solid phase, the solid phase may be washed with weak alkaline water, if necessary.
[0054] <Oxidation process> Next, the nickel-containing hydroxide particles on which the coating layer containing cobalt is formed are oxidized. The method of the oxidation treatment includes adding an alkaline solution such as an aqueous sodium hydroxide solution to the dry powder of the nickel-containing hydroxide particles on which the coating layer containing cobalt is formed, mixing, and heating. In this case, in order to quickly evaporate the water content of the aqueous sodium hydroxide solution, it is preferable to oxidize at 110°C or higher, more preferably 115°C or higher, and particularly preferably 120°C or higher. In addition, it is preferable to heat the cobalt-coated nickel-containing hydroxide particles to 60°C in advance, add an alkaline solution such as an aqueous sodium hydroxide solution, and further heat the particles for oxidation treatment. Since the water content evaporates quickly by the above oxidation treatment, the divalent cobalt in the nickel-containing hydroxide particles on which the coating layer containing cobalt is formed can be oxidized to cobalt oxyhydroxide, which is trivalent cobalt. By oxidizing the divalent cobalt in the coating layer to cobalt oxyhydroxide, the cobalt-coated nickel-containing hydroxide particles of the present invention on which the coating layer containing cobalt oxyhydroxide is formed can be obtained.
[0055] In the cobalt-coated nickel-containing hydroxide particles of the present invention, the relative error between the value A before compression treatment at a press pressure of 64 MPa and the value B after compression treatment at a press pressure of 64 MPa, in terms of the area size of the region where the maximum peak height is 1 / 2 or more, is controlled to be -1.50 or more and 5.00 or less, mainly by adjusting the oxidation conditions in the oxidation step, such as the amount of alkaline solution added in the oxidation step. Specifically, in terms of the oxidation conditions in the oxidation step, the weight ratio of the nickel-containing hydroxide particles on which a coating layer containing cobalt is formed and the alkaline solution (concentration, for example, 32 to 48 mass%) is set to 1:0.1, so that the relative error in the area size of the region where the maximum peak height is 1 / 2 or more is controlled to be -1.50 or more and 5.00 or less.
[0056] <Solid-liquid separation process> In addition, after the oxidation step, if necessary, the method may further include a step of separating the suspension containing the cobalt-coated nickel-containing hydroxide particles into a solid phase and a liquid phase, and drying the solid phase separated from the liquid phase. In addition, if necessary, the solid phase may be washed with weak alkaline water before drying.
[0057] Next, a positive electrode using the cobalt-coated nickel-containing hydroxide particles of the present invention and a secondary battery using the positive electrode will be described. Here, a nickel-hydrogen secondary battery will be taken as an example of the secondary battery. The nickel-hydrogen secondary battery includes a positive electrode using the cobalt-coated nickel-containing hydroxide particles of the present invention described above, a negative electrode, an alkaline electrolyte, and a separator.
[0058] The positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the surface of the positive electrode current collector. The positive electrode active material layer includes cobalt-coated nickel-containing hydroxide particles, a binder, and, if necessary, a conductive assistant. The conductive assistant is not particularly limited as long as it can be used for nickel-hydrogen secondary batteries, and metal cobalt or cobalt oxide can be used. The binder is not particularly limited, and examples thereof include polymer resins such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE), and combinations thereof. The positive electrode current collector is not particularly limited, and examples thereof include punching metal, expanded metal, wire mesh, foam metal such as foamed nickel, mesh-like metal fiber sintered body, metal-plated resin plate, and metal foil.
[0059] In a method for producing a positive electrode, for example, first, cobalt-coated nickel-containing hydroxide particles, a binder, water, and optionally a conductive additive are mixed to prepare a positive electrode active material slurry, which is then filled into a positive electrode current collector by a known filling method, dried, and then rolled and fixed by a press or the like.
[0060] The negative electrode comprises a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material formed on the surface of the negative electrode current collector. The negative electrode active material is not particularly limited as long as it is a commonly used material, and examples thereof include hydrogen storage alloys. The negative electrode current collector may be made of a conductive metal material such as nickel, aluminum, or stainless steel.
[0061] If necessary, the negative electrode active material layer may further contain a conductive assistant, a binder (binding agent), etc. Examples of the conductive assistant and binder include the same ones as those used in the positive electrode active material layer.
[0062] In a method for producing a negative electrode, for example, a negative electrode active material is first mixed with an electroconductive assistant and a binder, if necessary, and water to prepare a negative electrode active material slurry, which is then filled into a negative electrode current collector by a known filling method, dried, and then rolled and fixed by a press or the like.
[0063] In the alkaline electrolyte, for example, the solvent may be water, and the solute to be dissolved in the solvent may be potassium hydroxide or sodium hydroxide. The above solutes may be used alone or in combination of two or more kinds.
[0064] The separator is not particularly limited, but examples thereof include polyolefin nonwoven fabrics such as polyethylene nonwoven fabrics and polypropylene nonwoven fabrics, polyamide nonwoven fabrics, and those which have been subjected to a hydrophilic treatment. EXAMPLES
[0065] Next, examples of the present invention will be described, but the present invention is not limited to these examples as long as they do not depart from the spirit of the present invention.
[0066] Example 1 Synthesis of nickel-containing hydroxide particles An aqueous solution of ammonium sulfate (complexing agent) and an aqueous solution of sodium hydroxide were dropped into an aqueous solution in which zinc sulfate and nickel sulfate were dissolved in a molar ratio of 2.0:98.0, and the pH in the reaction vessel was maintained at 12.0 at a liquid temperature of 25°C, while the mixture was continuously stirred with a stirrer. The hydroxide formed was allowed to overflow from the overflow pipe of the reaction vessel and was taken out. The hydroxide taken out was subjected to the processes of washing with water, dehydration, and drying to obtain nickel-containing hydroxide particles.
[0067] Formation of a coating layer containing cobalt The dry powder of nickel-containing hydroxide particles obtained as described above and warm water at 45°C were mixed in a weight ratio of 1.0:2.0 and fed to a reaction tank, and then warm water was added to the reaction tank to obtain a predetermined suspension concentration. After the nickel-containing hydroxide particles were added, a cobalt sulfate aqueous solution with a concentration of 90g / L was added dropwise while stirring the solution. During this time, a sodium hydroxide aqueous solution was appropriately added dropwise to maintain the pH of the solution in the reaction tank in the range of 9 to 13 based on a liquid temperature of 25°C, forming a coating layer of cobalt hydroxide on the surface of the hydroxide particles, and a suspension of nickel-containing hydroxide particles coated with cobalt hydroxide was obtained.
[0068] Oxidation treatment of nickel-containing hydroxide particles coated with cobalt hydroxide The suspension of nickel-containing hydroxide particles coated with cobalt hydroxide obtained as described above was subjected to solid-liquid separation, and the solid phase was dried to obtain a dry powder of nickel-containing hydroxide particles coated with cobalt hydroxide. Next, the nickel-containing hydroxide particles coated with cobalt hydroxide were heated to 60°C, and then further heated and stirred, while supplying 48% by mass of sodium hydroxide aqueous solution so that the weight ratio of nickel-containing hydroxide particles coated with cobalt hydroxide to the alkaline solution was 1:0.10, and heating to 120°C to perform oxidation treatment. In the above oxidation treatment, the cobalt hydroxide in the coating layer of the nickel-containing hydroxide particles was oxidized to obtain cobalt oxyhydroxide, which is trivalent cobalt.
[0069] Solid-liquid separation and drying process Next, the oxidized nickel-containing hydroxide particles were subjected to treatments of washing with water, dehydration, and drying to obtain the cobalt-coated nickel-containing hydroxide particles of Example 1.
[0070] Comparative Example 1 Cobalt-coated nickel-containing hydroxide particles of Comparative Example 1 were obtained in the same manner as in Example 1, except that the weight ratio of the nickel-containing hydroxide particles coated with cobalt hydroxide to the alkaline solution in the oxidation treatment of Example 1 was 1:0.05.
[0071] Comparative Example 2 Cobalt-coated nickel-containing hydroxide particles of Comparative Example 2 were obtained in the same manner as in Example 1, except that the weight ratio of the nickel-containing hydroxide particles coated with cobalt hydroxide to the alkaline solution in the oxidation treatment of Example 1 was 1:0.20.
[0072] Comparative Example 3 Instead of the aqueous solution in which zinc sulfate and nickel sulfate were dissolved in a molar ratio of 2.0:98.0, an aqueous solution in which cobalt sulfate, zinc sulfate, and nickel sulfate were dissolved in a molar ratio of 4.5:5.0:90.5 was used as the additive metal element M. Cobalt-coated nickel-containing hydroxide particles of Comparative Example 3 were obtained in the same manner as in Example 1, except that in the coating step, warm water and the dry powder were mixed so as to have a predetermined suspension concentration from the beginning, and in the oxidation step, the temperature during the oxidation treatment was set to 100°C since a large amount of the additive metal element M was contained.
[0073] Evaluation items (1) Measurement of volumetric particle size distribution by laser diffraction scattering method For each of the cobalt-coated nickel-containing hydroxide particles obtained in Example 1 and Comparative Examples 1 to 3, before pressing, the volumetric particle size distribution was measured by a laser diffraction scattering method using a particle size distribution measuring device (manufactured by Horiba, Ltd., "LA-950") under conditions of solvent: water, solvent refractive index: 1.33, particle refractive index: 2.13, transmittance 80±5%, and dispersion medium: 10.0 wt% sodium hexametaphosphate aqueous solution, and a volumetric particle size distribution diagram was obtained. In addition, for the cobalt-coated nickel-containing hydroxide particles of Example 1 and Comparative Examples 1 to 3, a compression press device (manufactured by Mitsubishi Chemical Analytech Co., Ltd., MCP-PD51 type) was used to put 3.00 g of the sample into a sample-injection cell with a radius of 10 mm, and the sample was compressed there under a load of 20 kN (press pressure of 64 MPa). Similarly, for the cobalt-coated nickel-containing hydroxide particles after pressing, a particle size distribution measuring device (manufactured by Horiba, Ltd., "LA-950") was used to measure the volumetric particle size distribution by a laser diffraction scattering method under the conditions of solvent: water, solvent refractive index: 1.33, particle refractive index: 2.13, transmittance 80±5%, and dispersion medium: 10.0 wt% sodium hexametaphosphate aqueous solution, and a volumetric particle size distribution diagram was obtained. Using the volumetric particle size distribution diagram before pressing, a value A indicating the extent of the area size of the region where the height of the maximum peak before pressing is 1 / 2 or more was calculated using formula (1). In addition, using the volumetric particle size distribution diagram after pressing, a value B indicating the extent of the area of the region in which the height of the maximum peak after pressing is 1 / 2 or more was calculated using formula (2). Furthermore, the relative error between value A and value B was calculated using formula (3).
[0074] (2) D50 From the results of measuring the volume-based particle size distribution before pressing by the laser diffraction scattering method described above in (1), D50 of the cobalt-coated nickel-containing hydroxide particles before pressing was obtained.
[0075] (3) Tap density (TD) The tap density of the cobalt-coated nickel-containing hydroxide particles (before pressing) obtained in Example 1 and Comparative Examples 1 to 3 was measured by the constant volume measurement method among the methods described in JIS R1628 using a tap denser (manufactured by Seishin Enterprise Co., Ltd., "KYT-4000").
[0076] (4) Bulk density (BD) For the cobalt-coated nickel-containing hydroxide particles (before pressing) obtained in Example 1 and Comparative Examples 1 to 3, the samples were allowed to fall naturally and filled into a container, and the bulk density was measured from the volume of the container and the mass of the samples.
[0077] (5) BET specific surface area 1 g of the cobalt-coated nickel-containing hydroxide particles (before pressing) obtained in Example 1 and Comparative Examples 1 to 3 was dried in a nitrogen atmosphere at 105°C for 30 minutes, and then measured by the one-point BET method using a specific surface area measuring device ("Macsorb" manufactured by Mountec Co., Ltd.).
[0078] (6) Volume resistivity The volume resistivity (Ω·cm) of the cobalt-coated nickel-containing hydroxide particles (before pressing) obtained in Example 1 and Comparative Examples 1 to 3 was measured using a powder resistivity system (Loresta) MCP-PD51 manufactured by Mitsubishi Chemical Analytech Corporation under the following conditions. Probe used: Four-point probe Electrode spacing: 3.0mm Electrode radius: 0.7mm Sample radius: 10.0 mm Sample mass: 3.00g Applied pressure: 20kPa
[0079] (7) Capacity maintenance rate The cobalt-coated nickel-containing hydroxide particles (before pressing) obtained in Example 1 and Comparative Examples 1 to 3 were activated by performing 8 cycles of charge and discharge at 0.2 C. The activated cobalt-coated nickel-containing hydroxide particles were subjected to a high-temperature standing treatment in which a 10Ω resistor was connected and left at 50° C. for 10 days. The cobalt-coated nickel-containing hydroxide particles after activation and the cobalt-coated nickel-containing hydroxide particles after the high-temperature standing treatment were charged and discharged at 0.2 C to measure the discharge capacity (P) of the cobalt-coated nickel-containing hydroxide particles after activation and the discharge capacity (Q) of the cobalt-coated nickel-containing hydroxide particles after the high-temperature standing treatment, and the capacity retention rate was calculated by the formula (discharge capacity (Q) of the cobalt-coated nickel-containing hydroxide particles after the high-temperature standing treatment / discharge capacity (P) of the cobalt-coated nickel-containing hydroxide particles after activation)×100.
[0080] For the cobalt-coated nickel-containing hydroxide particles of Example 1 and Comparative Examples 1 to 3, the volumetric particle size distribution diagrams obtained by the laser diffraction scattering method are shown in FIG. 2. The value A calculated by formula (1) using the volumetric particle size distribution diagram before pressing, the value B calculated by formula (2) using the volumetric particle size distribution diagram after pressing, and the relative error between the values A and B calculated by formula (3) are shown in Table 1 below. The D50, tap density (TD), bulk density (BD), BET specific surface area, volume resistivity, and capacity retention rate are shown in Table 2 below.
[0081] [Table 1]
[0082] [Table 2]
[0083] As can be seen from Tables 1 and 2 above, the cobalt-coated nickel-containing hydroxide particles of Example 1, which have a composition in which the molar percentage ratio of nickel:zinc:additive metal element M is 100-xy:x:y (1.50≦x≦9.00, 0.00≦y≦3.00) and in which the relative error between value A indicating the extent of the area size of the region where the height of the maximum peak is 1 / 2 or more before pressing and value B indicating the extent of the area size of the region where the height of the maximum peak is 1 / 2 or more after pressing is -1.50 or more and 5.00 or less, had excellent electrical conductivity with a volume resistivity of 0.82 Ω cm. Therefore, in Example 1 having a composition in which the molar ratio of nickel:zinc:additive metal element M is 100-xy:x:y (1.50≦x≦9.00, 0.00≦y≦3.00), it was found that when the cobalt coating of the nickel-containing hydroxide particles was oxidized, the volume resistivity was reduced because the cobalt coating was sufficiently oxidized while preventing the aggregation of the nickel-containing hydroxide particles. In addition, in the cobalt-coated nickel-containing hydroxide particles of Example 1, the capacity retention rate calculated from the discharge capacity after activation and the discharge capacity after high-temperature storage treatment was 96.3%, and an excellent capacity retention rate was obtained even after high-temperature storage treatment. Therefore, it was found that the secondary battery equipped with the cobalt-coated nickel-containing hydroxide particles of Example 1 can exhibit excellent battery characteristics even when operated in a severe environment such as high temperature and under a high load.
[0084] Furthermore, in the case of the cobalt-coated nickel-containing hydroxide particles of Example 1, the D50, tap density (TD), bulk density (BD), and BET specific surface area were all comparable to those of the conventional particles, and thus the properties other than the relative error before and after pressing with respect to the area of the region where the height of the maximum peak is 1 / 2 or more and the volume resistivity were not impaired.
[0085] On the other hand, from Tables 1 and 2, in the cobalt-coated nickel-containing hydroxide particles of Comparative Example 1, in which the oxidation treatment was performed at a weight ratio of nickel-containing hydroxide particles coated with cobalt hydroxide and an alkaline solution of 1:0.05, the relative error was -1.62, and the volume resistivity was 1.30 Ω·cm, and good electrical conductivity was not obtained. Therefore, in Comparative Example 1, it was found that the volume resistivity could not be reduced because the cobalt coating was not sufficiently oxidized when the cobalt coating of the nickel-containing hydroxide particles was oxidized. In addition, in the cobalt-coated nickel-containing hydroxide particles of Comparative Example 1, the capacity retention rate calculated from the discharge capacity after activation and the discharge capacity after the high-temperature storage treatment was 91.9%, and a good capacity retention rate was not obtained when the high-temperature storage treatment was performed. Therefore, it was found that the secondary battery equipped with the cobalt-coated nickel-containing hydroxide particles of Comparative Example 1 cannot exhibit good battery characteristics when operated in a severe environment such as a high temperature and under a high load.
[0086] In addition, in the cobalt-coated nickel-containing hydroxide particles of Comparative Example 2, in which the oxidation treatment was performed at a weight ratio of nickel-containing hydroxide particles coated with cobalt hydroxide and an alkaline solution of 1:0.20, the relative error was -5.14, and the volume resistivity was 2.60 Ω·cm, and good electrical conductivity was not obtained. Therefore, in Comparative Example 2, it was found that even if the cobalt coating of the nickel-containing hydroxide particles was sufficiently oxidized when the cobalt coating was oxidized, the nickel-containing hydroxide particles were easily aggregated, and the volume resistivity could not be reduced. In addition, in the cobalt-coated nickel-containing hydroxide particles of Comparative Example 2, the capacity retention rate calculated from the discharge capacity after activation and the discharge capacity after high-temperature storage treatment was 87.7%, and a good capacity retention rate was not obtained when the high-temperature storage treatment was performed.
[0087] In addition, in the cobalt-coated nickel-containing hydroxide particles of Comparative Example 3 in which the molar ratio of nickel:zinc:additive metal element M was 90.5:5.0:4.5, the relative error was 7.27, and the volume resistivity was 67.5 Ω·cm, and good electrical conductivity was not obtained. In Comparative Example 3, it is considered that the oxidation of the coating layer in the oxidation step was inhibited because the additive metal element M was 3.00 or more, and the volume resistivity could not be sufficiently reduced. In addition, in the cobalt-coated nickel-containing hydroxide particles of Comparative Example 3, the capacity retention calculated from the discharge capacity after activation and the discharge capacity after high-temperature storage treatment was 85.0%, and a good capacity retention rate was not obtained when the high-temperature storage treatment was performed. [Industrial Applicability]
[0088] When the cobalt-coated nickel-containing hydroxide particles of the present invention are installed in a nickel-hydrogen secondary battery as a positive electrode active material, the secondary battery can operate in harsh environments such as high temperatures and exhibit excellent battery characteristics even under high load conditions, and therefore can be used in all fields of nickel-hydrogen secondary batteries.
Claims
1. Cobalt-coated nickel-containing hydroxide particles, in which a coating layer containing cobalt oxyhydroxide as a main component is formed on nickel-containing hydroxide particles, The nickel-containing hydroxide particles contain nickel (Ni), zinc (Zn), and one or more added metal elements M selected from the group consisting of cobalt (Co) and magnesium (Mg), and the mole percent ratio of nickel:zinc:added metal element M is 100-x-y:x:y (meaning 1.50≦x≦9.00, 0.00≦y≦3.00); In the volume-based particle size distribution measured by a laser diffraction scattering method, the maximum peak has a height a; There is one peak at a height of (½)a or more, and the value A of the following formula (1) is calculated from the width b of the maximum peak at the height of (½)a, Cobalt-coated nickel-containing hydroxide particles, in which a volume-based particle size distribution measured by a laser diffraction scattering method after compression treatment at a press pressure of 64 MPa has a maximum peak with a height c, and has a value B of the following formula (2) calculated from a width d of the maximum peak at a height of (1 / 2)c, and the value B and the value A have a relationship represented by the following formula (3). A=[(b×(1 / 2)a] / 2...(1) B=[(d×(1 / 2)c] / 2...(2) -1.50≦[(B-A) / A]×100≦5.00...(3)
2. 2. The cobalt-coated nickel-containing hydroxide particles according to claim 1, wherein the volume-based particle size distribution before the compression treatment has one peak.
3. 3. The cobalt-coated nickel-containing hydroxide particles according to claim 1, having a volume resistivity of 0.40 Ω·cm or more and 1.20 Ω·cm or less.
4. The cobalt-coated nickel-containing hydroxide particles according to any one of claims 1 to 3, wherein the coating layer containing cobalt oxyhydroxide further contains cobalt oxide.
5. The cobalt-coated nickel-containing hydroxide particles according to claim 1 , wherein the nickel-containing hydroxide particles contain zinc.
6. The cobalt-coated nickel-containing hydroxide particles according to any one of claims 1 to 5, which are used as a positive electrode active material for a nickel-hydrogen secondary battery.
7. A positive electrode comprising the cobalt-coated nickel-containing hydroxide particles according to any one of claims 1 to 6 and a metal foil current collector.
8. A nickel-metal hydride secondary battery comprising the positive electrode according to claim 7.
Citation Information
Patent Citations
Alkaline storage battery and its manufacture
JP1998334913A
Nickel positive electrode active material for alkaline secondary battery and manufacturing method of cobalt compound-coated nickel hydroxide particle
JP2003157840A
Method for producing cobalt oxyhydroxide-coated nickel hydroxide
JP2012091955A
Positive electrode active material for alkali storage battery and alkali storage battery
JP2012150947A
Coated nickel hydroxide powder for positive electrode active material of alkaline secondary battery
JP2014103127A